Passively mode-locked erbium doped zirconia fiber laser using a nonlinear polarisation rotation technique - Hamzah, A.; Paul, Mukul Chandra; Awang, N.A.; Ahmad, Harith; Pal, M.; Das, S.; Ismail, M.A.; Harun, Sulaiman Wadi (Elsevier, 2013)
A nonlinear polarization rotation (NPR) based mode-locked fiber laser is demonstrated using a 2 m long erbium-doped Zirconia–Yttria–Allumino Silicate fiber (EDZF) as the gain medium. The EDZF is drawn from a silica preform fabricated using the Modified Chemical Vapor Deposition (MCVD) method in which glass modifiers and nucleating agents are added using the solution doping technique. The fabricated EDZF has a core with dopant concentrations of 0.25 mol% of Al2O3, 2.10 mol% of ZrO2 and 0.23 mol% of Er2O3, peak absorption of 22.0 dB/m at 978 nm and the fluorescence life-time of 10.86 ms. A stable picosecond laser is succesfully obtained with pulse width of 0.32 ps and the repetition rate of 50 MHz using a simple ring cavity.